Theoretical and experimental studies on concave mirror‐based fiber optic displacement sensor - Yang, Hang Zhou; Harun, Sulaiman Wadi; Ahmad, Harith (Emerald, 2011)
Purpose - The purpose of this paper is to investigate, theoretically and experimentally, a concave mirror-based fiber optic displacement sensor performance for three-axes directional measurements. Design/methodology/approach - Mathematical model is constructed based on spherical mirror properties of the concave mirror and the simulated result is found to be in good agreement with the experimental results. Findings - Both theoretical and experimental results show that the focal length and radius of the concave mirror make significant influence to the displacement response. In the x-axes measurement, six linear slopes are obtained with four of them are located in the vicinity of the position, two times of the focal length. The maximum measurement range of about 20mm is obtained using a focal length of 10 mm. In the y- and z-axes displacement measurements, the linear range increases as the diameter of concave mirror increases. The longest linear range of 8mm is achieved at mirror radius of 10 mm. Originality/value - This is the first demonstration of three axes directional displacement measurements using a concave mirror as a target.